Ergonomic assessment of wheel hoe and design compliance for women farm worker - SINHA, JAYA; SINGH, J K; KUMAR, ADARSH (The Indian Journal of Agricultural Sciences, 2023)
Weeding is carried out by women farm workers with hand tools and most of these tools are operated in squatting or bending posture. These tools are essentially designed for male farm workers. One of the common hand tool used for weeding is wheel hoe. Therefore, ergonomic assessments of an existing wheel hoe and design modification were done to make it compatible for women workers. The wheel hoe was ergonomically evaluated for physiological and postural parameters. Mismatches were observed between required energy and sustainable energy output and between tool dimensions and anthropometric measurements of female operators. Based on the ergonomic evaluation the hoe was modified with two blade sizes and three handle widths .The modified wheel hoes were re-evaluated. Working with an existing wheel hoe was categorized as â€œheavy workâ€ with â€œhigherâ€ overall discomfort. Heart rate, oxygen consumption and energy expenditure were lowest for modified weeder (10%-440mm) and the work classification improved to â€œmoderate categoryâ€. The resting period with the modified hoe reduced from 33.4 min to 20.7 min for one hour work cycle. With change in handle dimensions shoulder, elbow and wrist deviation were close to the natural range of motion. The body part discomfort score and overall discomfort score also reduced from 31 and 2.5 respectively to 18 and 1.5 for modified weeder (10%-440mm). Women workers found the modified hoe with 10% blade dimension and handle width 440mm, very comfortable to use. Modifications in the existing wheel hoe according to anthropometric parameters of female workers reduced energy consumption, body deviations and rest pause between work cycles and thus enhanced work output.